The impact of the Arabian Nights in Modern Egyptian narration: Mahfouz’s Arabian Nights and Days as a Case Study - Elgayyar, Sherif (Scripta Neophilologica Posnaniensia, 2021)
The Arabian Nights were passed orally for long eras, long before they were written down; the collective sense, through several anonymous narrators, developed them: changing, modifying, omitting and adding to this oral discourse. All for the purpose of entertaining the public according the spirit of the age and the socio-cultural contexts, afterwards, it was recorded in different versions, as diverse as their sources, up until the landmark version, namely the one printed in Bulak, Egypt in 1835.The West is to be commended on paying attention to the significance of The Arabian Nights, academically and creatively, before its original-home, especially since it was later translated to many languages. After French orientalist Antoine Galland (1646 - 1715) translated into French between 1704 and 1713 a third of the manuscript he had brought from the Orient.This study delves into “The Impact of The Arabian Nights on Modern Egyptian Narration”. The researcher tries to point out how Egyptian writers were inspired by the classic text by examining Naguib Mahfouz's Arabian Nights and Days (Layālī alf laylah) as a case study. An analytic, text-based approach was used to detect the intertextual interaction between the classic and the modern, and to explore how classical elements and connotations were employed within the modern text.